Simulating Democracy: Emancipation of Democracy Crisis in Dubravka Ugrešić’s Essays - Marot Kiš, Danijela (Poznańskie Studia Slawistyczne, 2019)
One of the central notions of the post-Yugoslav literature is the status of democracy in national states formed after the breakup of Yugoslavia. From the perspective of the exile, not only as banishment, but also as a liberating outside view into the once common social, cultural and political space, the post-Yugoslav writers question the social democracy praxis in their former home states comparing it to the social practices in the states of their current residence. In her books of essays, Dubravka Ugrešić ironizes different forms of social ideology in Croatia from the beginning of nineteen-nineties. Her writing recognizes the standards of European democracy accompanied with the ideological view into the questions of social rights, religion and language as the stumbling block of modern society. Ugrešić describes democracy as a notion hiding different things: the praxis of ruthless capitalist exploitation, loss of media freedom, media manipulation, the censorship of corporate capitalism, production of lies, modern slavery... (Don’t take it personal, 2014), validating in her essays the importance of literature in disclosure of autocracy masked as democracy.